(untitled) (Marketing Journal, 2025)
The article explores the tax discipline concept as an economic category from a scientific and theoretical point of view. It aims to study the issue of strengthening tax discipline in ensuring the country's financial security. Furthermore, the article inves tigates a developed mathematical apparatus using the method of econometric assessment of the impact of tax discipline on financial security – ARDL (autoregressive distributed lag) and their coefficient of long and short term dependence.